Conference Review: Reconstructive and Experimental Archaeology Conference REARC 2013 - David Wescott (EXARC, 2014)
The 4th Annual Reconstructive and Experimental Archaeology Conference was recently held in Gastonia, NC at the Schiele Museum of Natural History. The conference theme was Education and Reconstructive and Experimental Archaeology.